Home environment and experiences of preschool children in an urban community two case studies - De la Cruz, Charito D.
This research drew baseline data on early development among Filipinos particularly about the role of home environment and experience in the development of abilities. The research is a detailed description of what two three-year-olds, from low income families in urban Manila, do during their waking hours, utilizing the method of direct, moment-to-moment observation in their home and neighborhood. The author concluded that a successful preschool program has to involve parents in the educational process to augment and extend school activities at home. The lessons have to be incorporated and planned based on the everyday living of the child thus promoting growth and better development for the child.